Functional Endoscopic Orbital Decompression Surgery in Acute Rhinosinusitis with Orbital Complication : A Case Report - Lekatompessy, Michael; Kirana, Amanda P (Fakultas Kedokteran Universitas Pelita Harapan, 2021)
Introduction: Orbital complications secondary to acute rhinosinusitis can cause permanent vision loss and death if not treated promptly and appropriately. The prevalence of orbital complications due to rhinosinusitis is more common in children than adults, occurring in 3-4% of children with acute rhinosinusitis. Lamina papyracea in children has many dehiscences, the nasal cavity tends to be narrower and the mucosa is softer than in adults, therefore causing the spread of infection more easily from the sinuses to the eyes. Clinical presentation: a 4-year-old child presented with eye swelling and pus discharge in the right eye for 5 days before being admitted to the hospital, for which she was treated with medication and did not improve. On physical examination, there is a narrow nasal cavity, inferior turbinate edema, and hyperemia, mucopurulent discharge. CT scan and MRI revealed contrast enhancement in intraorbital with suspected intraorbital abscess with orbital cellulitis, right pansinusitis, and buccal abscess. Functional endoscopic orbital decompression was done immediately.Conclusion: Orbital complications due to acute rhinosinusitis are uncommon but potentially lead to more fatal complications. Early diagnosis and aggressive treatment of immediate functional endoscopic sinus surgery and antimicrobial therapy have a good outcome.